UPAYA HUKUM DALAM PENYELESAIAN PELANGGARAN DAN SENGKETA HAK KARYA CIPTA MUSIK - Maytasari Anindya, Fitria Trie; Wiryawan, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013)
Intellectual property rights is the right material derived from the work of the brain. The work in the form of immaterial objects such as works of song that comes from the workings of the brain where the brain work is defined as the intellect then called the Intellectual Property Rights. Violation of copyright ranged the desire for financial profit quickly by ignoring the creators or copyright holders. So in this paper we discuss how to solve the problem and remedies that can be done in case of violation of copyright musical works.
Keywords: Intellectual property rights, Violation, Remedy